Molecular Typing of Klebsiella pneumoniae Clinical Isolates by Enterobacterial Repetitive Intergenic Consensus Polymerase Chain Reaction - Parinaz Sedighi; Omid Zarei; Kiana Karimi; Mohammad Taheri; Pezhman Karami; Leili Shokoohizadeh (International Journal of Microbiology)
Aim. Klebsiella pneumoniae is one of the most important causes of nosocomial infections, including pneumonia, sepsis, and urinary tract infection. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) technique is a quick, reliable, and cost-effective method for molecular typing of Enterobacteriaceae family members. This study aimed to detect genetic relatedness among K. pneumoniae isolates from hospitals in Hamadan city, using ERIC-PCR technique. Materials and Methods. A total of 72 K. pneumoniae isolates were collected from patients admitted to Besat and Sina hospitals. After detection and confirmation of K. pneumonia isolates by chemical and conventional microbiological methods, DNAs were extracted after 24 hours of incubation at 37°C, using the boiling method. ERIC-PCR technique was carried out, and the ERIC patterns were analyzed by online data analysis service (inslico.ehu.es). ERIC profiles were compared using Dice method and clustered by UPGMA (unweighted pair group method with arithmetic mean) program. Also, the samples were evaluated by PCR method for the detection of aerobactin gene within their genome. Finding. The genetic relatedness among K. pneumoniae isolates was studied, and results established the genetic diversity of the clinical isolates by detecting 25 different ERIC types, including 14 common types and 11 unique types. Also, none of the isolates had aerobactin gene. Discussion. The results of this study showed high genetic diversity among K. pneumoniae strains, indicating the polyclonal distribution of K. pneumoniae isolates in Hamadan hospitals. This diversity causes problems for the treatment of infections due to the circulation of diverse K. pneumoniae clones, which possibly have different antimicrobial susceptibility patterns.